Parámetros fisiológicos de hembras caninas sometidas a dos protocolos anestésicos en Oforosalpingohisterectomía durante la etapa postoperatoria - Aveiga Dueñas, Darío Javier (2021)
This research work was developed at the veterinary "Dr. Miller” in Chone city, Manabí Province. The behavior of the parameters was determined by evaluating the physiological variables of female canine undergoing two anesthetic protocols in oforosalpingohysterectomy, during the postoperative stage. Forty canine females from 1 to 3 years of age were used, which were randomly distributed in two treatments: Treatment 1 with Lidocaine Hydrochloride 2% as an intraoperative analgesic and treatment 2 with Fentanyl Citrate 0.005%. In each treatment, the physiological variables were evaluated in the postoperative period (heart rate, respiratory rate, mean arterial pressure, temperature, pulse oximetry, extubation time). A comparison of groups and Tukey's test (0.05%) were performed, showing significant differences in the heart rate parameter from the start of the monitoring to the end. During the monitoring, both treatments showed a decreasing body temperature to a minimum of 36ºC, but at minute 120 significant differences of 38°C were reflected in Treatment 1 and in Treatment 2 of 38.4°C. Treatment 1 turned out to be more economical, being 0.11 cents per ml, with a total cost of 1.86 dollar, the total amount used was 16.9 ml, while in Treatment 2 the value for each ml administered was 1 dollar, 68.4 ml were used in total, having a total cost of 68.40 dollars.